Features of dynamics of the instabilities at presence multiplicative fluctuation - Buts, V.A.; Buts, A.V.; Serikov, S.A. (Вопросы атомной науки и техники, 2003)
Dynamics of systems, which parameters are subject to random influences, is considered. The random affect can be as external, and be caused by own chaotic dynamics of system. The important features of dynamics of such systems are allocated: their behavior has an intermittence character; in these systems (even linear) the properties characteristic for a stochastic resonance can be shown; instability, which are caused by noise, practically are not stabilized by nonlinearities.